2016
DOI: 10.1016/j.bbr.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Studies of mice with cyclic AMP-dependent protein kinase (PKA) defects reveal the critical role of PKA’s catalytic subunits in anxiety

Abstract: Cyclic adenosine mono-phosphate-dependent protein kinase (PKA) is critically involved in the regulation of behavioral responses. Previous studies showed that PKA's main regulatory subunit, R1α, is involved in anxiety-like behaviors. The purpose of this study was to determine how the catalytic subunit, Cα, might affect R1α's function and determine its effects on anxiety-related behaviors. The marble bury (MB) and elevated plus maze (EPM) tests were used to assess anxiety-like behavior and the hotplate test to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…Our finding of a lack of a genotype effect in other behavioral assays of anxiety in adolescent mice suggest that the anxiety-like phenotype as noted in adult mice with loss of one Prkar1a allele (associated with increased PKA activity in the amygdala), is likely due to long-term exposure during critical developmental periods of brain development to alterations in PKA activity. PKA activity in brain areas of adolescent WT and HZ mice are similar to what has been reported for their adult counterparts (unpublished data); namely, increased PKA activity in the amygdala but no genotype differences in PKA activity in cortex, thalamus, or paraventricular hypothalamus [10, 11].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our finding of a lack of a genotype effect in other behavioral assays of anxiety in adolescent mice suggest that the anxiety-like phenotype as noted in adult mice with loss of one Prkar1a allele (associated with increased PKA activity in the amygdala), is likely due to long-term exposure during critical developmental periods of brain development to alterations in PKA activity. PKA activity in brain areas of adolescent WT and HZ mice are similar to what has been reported for their adult counterparts (unpublished data); namely, increased PKA activity in the amygdala but no genotype differences in PKA activity in cortex, thalamus, or paraventricular hypothalamus [10, 11].…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have demonstrated that PKA’s main regulatory subunit, R1α, is involved in the expression of anxiety-like behaviors; the loss of one Prkar1a allele in mice ( Prkar1a +/− ) led to an augmentation of anxiety-like behaviors in association with an increase in PKA activity in both the basolateral (BLA) and central amygdala (CeA) [10]. In a subsequent study, Briassoulis et al [11] studied the effects of deleting one allele of the main catalytic subunit (Cα) and compared anxiety-related behaviors in Prkar1a +/− and Prkar1a +/− /Prkaca +/− mice: the former spent significantly less time in the open arms of the elevated plus maze (EPM), while Prkaca +/− and Prkar1a +/− /Prkaca +/− mice displayed less exploratory behaviors [11].…”
Section: Introductionmentioning
confidence: 99%
“…The alteration of PKA activity in these transgenic mice was not a ubiquitous effect, since PKA activity was found to be similar between heterozygotes and WT mice in some brain areas (e.g., prefrontal cortex, hippocampus, paraventricular hypothalamus, cerebellum, and neural sensory areas). These findings highlight the importance of even modest changes in PKA activity in modulating anxiety-like behaviors and also that catalytic subunit activity is not the sole determinant of PKA’s cAMP-signaling effects ( 89 , 90 ). It is also possible that compensatory mechanisms in remaining PKA subunits and PDE4 may be a factor in areas not showing any differences in PKA activity between Prkar1a +/− and Prkar1a +/− /Prkaca +/− and WT or Prkaca +/− mice.…”
Section: Effect Of Pka Defects On Anxiety-like Behaviormentioning
confidence: 96%
“…PKA mouse models have also demonstrated a role for PKA signaling in anxiety. Increased cAMP signaling has been associated with an anxiety phenotype in mice that were haploinsufficient for either Prkar1a (Keil et al 2012) or Prkaca (Briassoulis et al 2016). Similarly, in mice overexpressing G s α, enhanced striatal PKA enzymatic activity was associated with an anxiety phenotype (Favilla et al 2008).…”
Section: Journal Of Endocrinologymentioning
confidence: 99%